A comprehensive clinical diagnostic score system for prediction of coronary artery spasm in patients with acute chest pain. (March 2019) - Lin, Yaowang; Qin, Haiyan; Chen, Ruimian; Liu, Qiyun; Liu, Huadong; Dong, Shaohong
Abstract: Background: Currently, there is no validated multivariate model to predict probability of coronary artery spasm (CAS) in patients with acute chest pain. Methods: A total of 976 consecutive patients with acute chest pain were enrolled. Patients were divided into two groups based on the presence of significant CAS. To adjust potential confounders, a multivariable analysis was performed and a clinical diagnostic score system for CAS was utilized for score derivation. Results: Multivariable analysis model selected 6 predictors for CAS. The integer score was assigned to each predictors: angina at rest alone (10 points), positive of hyperventilation test (8 points), allergies (3 points), asthma, ST-segment elevation and myocardial bridge (2 points each). We showed that the clinical diagnostic score system had accuracy in predicting CAS, as measured by the area under the curve (AUC), which was 0.952–0.966. The cut-off baseline value for the clinical diagnostic score system was set to 11–12 points with specificity of 91.0–93.3% and sensitivity of 90.7–92.9%, respectively. Conclusion: A clinical diagnostic score system was derived and validated as an accurate tool for estimating the pretest probability of CAS in patients with acute chest pain.